Severe Hyperkalemia and Bilateral Adrenal Metastasis. (10th February 2010) - Nagler, Michael; Müller, Beat; Briner, Verena; Winterhalder, Ralph
Abstract : Adrenal metastases are a common finding in metastatic lung and breast cancer. Often there are no clinical symptoms suggesting them. In this paper, we present a case of a 66-year-old man with metastatic lung cancer suffering from severe hyperkaliemia due to hypoaldosteronism as a result of bilateral adrenal metastasis.